Integrating Religion Moderation on Pancasila Student Profile at Elementary School - Septikasari, Resti; Dewi, Tri Ratna; Yuliantoro, Ahmad Taufiq (JIP Jurnal Ilmiah PGMI, 2023)
Problem in study This started with exists National Medium Term Development Plan (RPJMN) at the Ministry of Religion that is strengthening moderation religion and plans Strategic at the Ministry of Education and Culture that is strengthening Profile Pancasila students, which of second matter this is very related. The aim of this research is to know integration mark moderation religion on profile student Pancasila in Elementary School. This research uses a literature review method which is carried out in various stages, namely determining themes, identifying keywords, identifying sources of information (database used) , determining inclusion and exclusion criteria, collecting related articles, make notes of important things found in the article, write literature review articles. Research result This First, on dimensions have faith and piety to God Almighty, and have good morals glorious integrated with mark humanity and tolerance. Second, on dimensions global diversity integrated with mark respect to tradition. Third, mutual cooperation is integrated with mark humanity and tolerance. Fourth, independence integrated with values of non- violence and balance. Fifth, be creative Can integrated with mark commitment nationality. Sixth, reason critical integrated with mark balanced and committed nationality.